Electrospun 1D Ta3N5 -(O) nanofibers as advanced electrocatalysts for hydrogen evolution reaction in proton exchange membrane water electrolyser - Mukkavilli, Raghunath Sharma; Ichangi, Arun; Thiyagarajan, Ganesh Babu; Vollnhals, Florian; Wilhelm, Michael; Bhardwaj, Aman; Christiansen, Silke; Neelakantan, Lakshman; Mathur, Sanjay; Kumar, Ravi (Open Ceramics, 2022)
This study demonstrates the synthesis and characterisation of electrospun Ta3N5-(O) 1D-nanofibers for electrocatalytic hydrogen evolution reaction (HER) and its performance in a proton exchange membrane (PEM) water electrolyser. 1D nanofibers were synthesized by electrospinning of tantalum ethoxide/polyvinylpyrrolidone (PVP) sol followed by ammonolysis at varied temperatures (800–1000 °C). Elemental distribution of the nanofibers analysed through XPS, and bulk-EDS studies revealed an increase in surface oxygen concentration with an increase in nitridation temperature (from 900 °C to 1000 °C). The nanofibers were characterized to exhibit high electrocatalytic activity for hydrogen evolution reaction (HER) with a low overpotential of 320 mV to deliver 10 mA/cm2 in 0.5 M H2SO4 electrolyte. The Ta3N5-(O) 1D nanofibers were employed as novel electrocatalyst without any conducting supports in a PEM water electrolyser. A current density of 0.1 A/cm2 was achieved at an applied voltage of 2 V which is on par with earth-abundant electrocatalysts like MoS2. Furthermore, the electrospun nano fibers showed excellent stability with negligible losses over 6 h of prolonged operation. The study demonstrates the advantage of nanostructuring the electrocatalysts in enhancing the applicability of Ta3N5 and paves further a path for the development of high performance 1-D electrocatalysts for hydrogen evolution reactions (HER).
CRIS-Team Scopus Importer:2023-03-07